Constructing Scientific Controversy: Framing Liberation Therapy for Multiple Sclerosis in Canadian Mainstream Press - Tulk, Brianne (Université d'Ottawa | University of Ottawa, 2013)
Liberation therapy has received significant attention in Canadian media as a controversial new surgical treatment for multiple sclerosis (MS). The wavering stance of the Canadian Institute of Health Research to fund clinical trials informed contentious media representations rooted in scientific expertise versus patient advocacy and hope. This research supports the finding of preceding media studies in scientific controversies that the conflict was defined by: a) A balance ethic giving equal weight to competing stakeholders, b) Socially constituted moral issues were dominated by a patient injustice frame, and c) A strong emphasis placed on stakeholders made up of patients or affected individuals to dominate the media framing and discourse. Through an in-depth case study informed by the sociology of scientific knowledge, this research argues that not only did the moral amplification of the patient injustice frame give salience to certain facts over others, but it also contributed to the social determination of research priorities.